Global NPP and straw bioenergy trends for 2000–2014. (July 2016) - Tum, M.; Zeidler, J.N.; Günther, K.P.; Esch, T.
Abstract: The ability of terrestrial ecosystems to sequestrate carbon and the use of cultivated land for food and bioenergy are both affected by large scale meteorological phenomena and climate change. In this study we used the Biosphere Energy Transfer Hydrology (BETHY/DLR) model to compute global Net Primary Productivity (NPP) on 1 km 2 resolution for the fifteen years 2000–2014. We found a global average of 60.2 Pg carbon per year, with the main contribution from the Tropics. Extending pre-existing studies with our results revealed a surprisingly low positive global trend in NPP of 0.04 Pg y −1 for the past 30 years. To bring NPP into application we used it to derive straw bioenergy potentials. For agricultural areas we found a global average bioenergy potential of 35.9 EJ y −1 . On a regional level as e.g. the "Wheat belt" in Western-Australia we found an interannual variability of up to ±40%, due to climate events (i.e. ENSO). Highlights: The global average NPP for the period 2000–2014 is 60.2 Pg y −1 (±3.0 Pg y −1 ). Over the last 30 years NPP increased by 0.03 Pg per year. The global straw energy potential is 35.9 EJ (±1.6 EJ) per year.